Torpedo - KATHERINE C. EPSTEIN (Harvard University Press, 2014)
â€œOur arms must be mighty, ready for instant action,â€ President Dwight D. Eisenhower informed his fellow citizens in his 1961 Farewell Address, â€œso that no potential aggressor may be tempted to risk his own destruction.â€ The need for constant preparedness and instantaneous readiness in turn demanded â€œan immense military establishment and a large arms industry,â€ the conjunction of which was â€œnew in the American experience.â€ In the most famous passage of his speech, Eisenhower warned, â€œ[W]e must guard against the acquisition of unwarranted influence, whether sought or unsought, by the military-industrial complex.â€ Although the military-industrial complex is difficult to define, its meaning was clear enough for Eisenhower. It formed the vanguard of a broader political-economic transformation, one that involved â€œthe very structure of our society.â€ In an effort to defend against the external Soviet threat, Eisenhower feared, the United States would destroy itself from within. Defense contractors and a â€œscientific-technological eliteâ€ could hijack public policy, while defense spending could throw off the proper â€œbalance between the public and private economyâ€ and make government contracts â€œvirtually a substitute for intellectual curiosityâ€ in academia. As private interests corrupted public ones, and vice versa, core American liberties, like the free market and the free university, would give way. The United States would become a garrison state, its freedoms eroded in peacetime as previously they had been eroded only in wartime, and its people asked to make sacrifices once asked only of soldiers. In both time and space, therefore, the exigencies of preparing for modern war would collapse the distinctions between war and peace, between battlefront and home front, and between state and society.1